Changes in the properties and organization of human lens lipid membranes occurring with age - Mainali, Laxman (Curr Eye Res, 2016)
PURPOSE: This research was undertaken to document the changes in the organization and properties of human lens lipid membranes that occur with age. MATERIALS AND METHODS: Human lens lipid membranes prepared from the total lipids extracted from clear lens cortices and nuclei of donors from age groups 0–20 and 21–40 years were investigated. An electron paramagnetic resonance technique and nitroxide spin labels (analogues of phospholipids and cholesterol) were used. RESULTS: Two distinct lipid domains, the phospholipid-cholesterol domain (PCD) and the pure cholesterol bilayer domain (CBD), were detected in all investigated membranes. Profiles of the acyl chain order, fluidity, hydrophobicity, and oxygen transport parameter across discriminated coexisting lipid domains were assessed. Independent of the age-related changes in phospholipid composition, the physical properties of the PCD remained the same for all age groups and were practically identical for cortical and nuclear membranes. However, the properties of pure CBDs changed significantly with the age of the donor and were related to the size of the CBD, which increased with the age of the donor and was greater in nuclear than in cortical membranes. A more-detailed analysis revealed that the size of the CBD was determined mainly by the cholesterol content in the membrane. CONCLUSIONS: This paper presents data from four age groups: 0–20, 21–40, 41–60, and 61–70 years. Data from age groups 41–60 and 61–70 years were published previously. Combining the previously published data with those data obtained in the present work allowed us to show the changes in the organization of cortical and nuclear lens lipid membranes as functions of age and cholesterol. It seems that the balance between age-related changes in membrane phospholipid composition and cholesterol content plays an integral role in the regulation of cholesterol-dependent processes in fiber cell membranes and in the maintenance of fiber cell membrane homeostasis.